2020
DOI: 10.1111/vox.12879
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory effects after platelet transfusion: a review

Abstract: Background and ObjectivesPlatelet has been linked to thrombosis in several studies. Inflammation is closely intertwined with thrombosis and occurs consecutively; it is therefore conceivable that platelet transfusions perform an increasingly vital role in inflammation. As platelet transfusions have been a significant therapeutic approach in patients for decades, serious risks including viral transmission, bacterial sepsis and acute lung injury have been demonstrated by retrospective studies and randomized clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…When a global ROS reporter was used, cold storage was identified as a process that increases ROS generation, 20,22 while there was no increase in the level of superoxide species, 49 possibly due to SOD2 expressed by human PLT mitochondria 50 . Our study confirms the observation that long‐term cold storage results in dysmetabolic mitochondrial activity and ROS production, which may associate with increased inflammatory activation in vivo 51 …”
Section: Discussionsupporting
confidence: 81%
“…When a global ROS reporter was used, cold storage was identified as a process that increases ROS generation, 20,22 while there was no increase in the level of superoxide species, 49 possibly due to SOD2 expressed by human PLT mitochondria 50 . Our study confirms the observation that long‐term cold storage results in dysmetabolic mitochondrial activity and ROS production, which may associate with increased inflammatory activation in vivo 51 …”
Section: Discussionsupporting
confidence: 81%
“… 97 99 Furthermore, platelet transfusion might increase the proinflammatory response as well as the risk of VTE and PE in COVID-19. 99 , 100 Therefore, platelet transfusion should be considered carefully in COVID-19 patients.…”
Section: What Are the Knowledge Gaps?mentioning
confidence: 99%
“…The detected plasma protein levels of the rats indicated that none of the rat administered with PPMO showed the plasma osmotic pressure alteration in sub-chronic toxicity study. PLT is a component of blood that reacts to bleeding from blood vessel injury by clumping, thereby initiating a blood clot 32) . The detected PLT levels suggested that the rat administrated with PPMO did not alter the blood coagulation function in sub-chronic toxicity study.…”
Section: Discussionmentioning
confidence: 99%